Transmasculinidade, corpo e cuidado de si: análise da transexualidade no Ambulatório TT [travestis e transexuais] da cidade de João Pessoa - Paraíba - Vale, Johnatan Ferreira Marques do (2018)
We live in a society that associates the biological sex to the gender to be taken over by the person. People that are adapted to this biological-gender sex are named “cisgender”. The study aimed the transsexuality, in other words, the transsexual person breaks with the associative admonition between the biologization perspective and the gender to be taken over. I specially focused in the social experience of transsexual men, that means, the ones who are designated when being born as women, because of his biological, genital and genetic apparatus, however, they want to be socially recognized as men. These trans men fight daily so that they can get social recognition and, as a consequence, adopt procedures that aim molder the body to the valid social expectations around the masculinity. To understand this process, the study was undertaken in the State Ambulatory for Shemales and Transsexual [TT Ambulatory] at Clementino Fraga Hospital, located at Jaguaribe [João Pessoa – Paraíba]. The general goal was to analyze the transition process of trans men, as well as the social uses of the body [rooted habits] (BOLTANSKI, 1989) that aims express a masculine performance. As a qualitative methodological strategy for corpus composition I used three interlinked techniques: 1) Participating observation of 30 medical appointments and socializations undertaken in the institutional-hospitable context, involving health professionals; 2) Analysis of 20 patient record of trans men registered in the transsexualizator protocol; 3) Eight semi structured interviews with trans men aged between 21 and 36 years that had periodical medical appointments at the specified ambulatory. As a complement, 4) I took part in a meeting with transsexual people and in a Regional Event of trans men. Based on Benedetti (2005) and Duque (2011), I gave a relevance to the corporeal modifications “external/temporary” (way of dressing, haircut, body language and language, packers used as simulacrum of penis, blinders used to disguise the breasts volume, for example), and “Internal/permanent” (hormone therapy, sexual surgeries) operated by the implied trans men, correlating the gender affirmation to a maintenance operation and montage. Many strategies for the corporal change are accomplished in the breaches of medical system, which is dangerous and harmful to the trans men accompanied. As the identity of masculine gender requires the affirmation, maintenance, social recognition and constant vigilance, according to Connel (2005), it evidences that its construction is made according to strict corporal normalizations. These procedures involve the pain approach, based on Le Breton (2005), because of the invasive and risky character of determined procedures. The inventory and the dense description of the corporeal modifications indicates that the social experience of transsexual virility/masculinity affirmation loads in its core, anguishes and sufferings, what produce, inclusively, deleterious effects for the people health.